2015
DOI: 10.1242/jeb.120394
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fates and effects of nitrite in brown trout under normoxic and hypoxic conditions: blood and tissue nitrite metabolism and interactions with branchialNOS,Na+/K+-ATPaseandhsp70expression

Abstract: Nitrite secures essential nitric oxide (NO) bioavailability in hypoxia at low endogenous concentrations, whereas it becomes toxic at high concentrations. We exposed brown trout to normoxic and hypoxic water in the absence and presence of added ambient nitrite to decipher the cellular metabolism and effects of nitrite at basal and elevated concentrations under different oxygen regimes. We also tested hypotheses concerning the influence of nitrite on branchial nitric oxide synthase (NOS), Na + /K + -ATPase (nka)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
(91 reference statements)
2
19
0
Order By: Relevance
“…Also, turbot exposed to nitrite in our study showed increased HSP70 level, which might reflect nitrite exposure caused tissue damage inducing the expression of HSP 70 (Deane and Woo, 2007;Jensen et al, 2015), and overexpression of HSP 70 entered blood (Madeira et al, 2012;SHENG et al, 2007).…”
Section: Discussionmentioning
confidence: 50%
“…Also, turbot exposed to nitrite in our study showed increased HSP70 level, which might reflect nitrite exposure caused tissue damage inducing the expression of HSP 70 (Deane and Woo, 2007;Jensen et al, 2015), and overexpression of HSP 70 entered blood (Madeira et al, 2012;SHENG et al, 2007).…”
Section: Discussionmentioning
confidence: 50%
“…Similar rise in NO production due to activation of iNOS expression has been demonstrated in hypoxic rainbow trout (Gerber et al, 2016, 2017). In addition, hypoxia has been shown to activate iNOS expression in brown trout (Jensen et al, 2015). Moreover, a protective role of iNOS against oxidative stress and ammonia tolerance has been reported in the hepatocytes of Magur catfish (Hasan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic actions of nitric oxide synthases (NOS) on l ‐arginine release NO in the presence of molecular oxygen and NADPH (Griffith & Stuehr, 1995). Among three NOS isoforms, constitutive neuronal NOS (nNOS) and inducible NOS (iNOS) are more active in teleost fishes (Andreakis et al, 2011; Cioni et al, 2019; Jensen et al, 2015). Generally, a small amount of NO is formed from l ‐arginine by nNOS, but during stress large amount of NO are released from inducible calcium‐independent iNOS in many cell types for a long period of time (Althaus, 2012; Choudhury & Saha, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations